(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The Resource Consumption Accounting (RCA) is currently a common concept as it provides a solution to many of German cost Management and the cost system based on Activity . This (RCA) has a main role in the cost rationalization process and allocation and management of resources in line with modern environmental and economic developments to achieve greater accuracy in allocating costs , better management of idle capacity and provide financial and non-financial data to support management decisions. The object of the research is to reduce costs by rationalizing the utilization of available resources by identifying the resources used, unused and idle to increase the profitability of products in the system of resource consumption accounting and its preference for the system of activity –based cost and The importance of research stems from the study of the application of modern administrative accounting tools, which is the activity cost-based cost system of and the system of resource consumption accounting and use in allocating costs in order to achieve a better allocation of these costs The researchers concluded that the system of resource consumption accounting works to reduce costs by reducing the cost of idle capacity from the unit cost and the possibility of exploiting this capacity by isolating it for the purpose of exploitation in production and this is broader than the goal of the ABC system, which only works to reallocate the costs and recommended that the application of the system RCA in Diyala company can analyze its activities to determine the value added of each activity and thus reduce the costs of activities that do not add value.